PENERAPAN MODEL PEMBELAJARAN INKUIRI UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS III SD NEGERI 035 SEKELADI KECAMATAN TANAH PUTIH KABUPATEN ROKAN HILIR - Aisyah, Siti Aisyah; Daud, Damanhuri Daud (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract :Problem background of this research that studentÂ  do not understand about IPA lesson. The average score result of IPAÂ  test is 58,80. And only 7 of 25 student or 28% in class can reach standard of KKM, while score of KKMÂ  is 75. This is the problem: âDo the Inkuiri Learning Model can improve IPA studying result,Â  Student of class III SD Negeri 035 Sekeladi Kecamatan Tanah Putih Kabupaten Rokan Hilir?â. This research form is Observation of Class Action/ Penelitian Tindakan Kelas (PTK). This is the hypothesis of this research: âIf the Direct Learning Model is applied therefore gets to increase IPA studying results, Student of class V SD Negeri 014 Pematang Sikek Kecamatan Rimba Melintang Kabupaten Rokan Hilir?â. This research is done as much 2 cycles with 6 appointments, there are 4 presentations and 2 times of test. After that, data is collected and analyzed. Test I (UH I) shows the increasing average score, from basic score 58,80 to be 71,90, its increase 13,10 points. And at the Test II (UH II) increase about 8,50 points. So that, the average score is to be 80,40 at the Test II. So, total increasing from basic score to Test II (UH II) is 21,60 points. The Classically Completing activity also increase about 32%, basic score percentage 28% at the Test I to be 60%. And at the Test II, percentage score is 84%, its increase 24%. Besides that, activity of teacher and student are increasing in every meeting. Percentage of teacher activity at the first meeting is 58,3%, and at the second is 66,7% (increase 8,4%). Fourth meeting, teacher activity is 75% (8,3%), and 91,7% (8,5%) at the fifth meeting. Student activity at the first meeting is 54,2%, and 65,5% (11,3%) at the second meeting. There is increasing to be 70,8% (5,3%) at the fourth meeting, and 91,7% (20,9%) at the fifth meeting. So, the conclusion is the Implementation of Inkuiri Learning Model can increase IPA studying result, Student of class III SD Negeri 035 Sekeladi Kecamatan Tanah Putih. Â  Keywords: Theory, Inkuiri Learning, IPA studying result Â